Development of a method for measuring rare earth elements in the environment for future experiments with gadolinium-loaded detectors - Ito, S; Okada, T; Takaku, Y; Harada, M; Ikeda, M; Kishimoto, Y; Koshio, Y; Nakahata, M; Nakajima, Y; Sekiya, H (Progress of theoretical and experimental physics, 2019)
Demand to use gadolinium (Gd) in detectors is increasing in the field of elementary particle physics, especially in neutrino measurements and dark matter searches. Large amounts of Gd are used in these experiments. To assess the impact of Gd on the environment it is becoming important to measure the baseline concentrations of Gd. Such measurement, however, is not easy due to interference by other elements. In this paper a method for measuring the concentrations of rare earth elements, including Gd, is proposed. In the method, inductively coupled plasma-mass spectrometry is utilized after collecting the dissolved elements in chelating resin. Results of the ability to detect anomalous concentrations of rare earth elements in river water samples in the Kamioka and Toyama areas are also reported.